A decision-making process for the selection of better ship main dimensions by a Pareto frontier solution. (1st November 2021) - Yurdakul, Onur; Küçüksu, Gözde Nur; Saydam, Ahmet Ziya; Çalışal, Mehmet Sander
Abstract: Initial ship design necessitates the evaluation of main ship parameters to obtain a feasible design solution satisfying the objectives. Traditionally, relationship between main dimensions and design parameters of proven designs provides a safe solution. This approach restrains the designer from improving the design with respect to conflicting design criteria. Pareto frontier technique has widely been utilized in the design of ships, mainly at advanced design stages for optimization problems. As the principal dimensions of a ship are also vital on the performance of the vessel, major improvements in performance may be achieved by selecting better principal dimensions. This paper proposes to integrate the Pareto technique to the design cycle at an early stage as a decision-making process for selection of better main dimensions with respect to multiple conflicting criteria A Pareto Front has been observed for two case studies (a destroyer and a planing craft) indicating a technological barrier for performance with respect to main dimensions. As the design process begins with main dimensions along the technological barrier, performance is improved with respect to conflicting design criteria at the beginning of the design process which serves as a better basis for further optimization studies to be conducted at advanced stages. Highlights: A decision-making process for selecting better main dimensions via Pareto frontier solutions are proposed. Process has been applied to a planing craft and a high speed destroyer hull. In both cases, better main dimensions are sought for improved seakeeping performance while also saving fuel. For both cases, a hull with better main dimensions could be obtained with the proposed process.